Signal Transducer and Activator of Transcription 3 in Keratinocytes Regulates Histaminergic Itch but Not Nonhistaminergic Itch - Takashi Hashimoto; Kent Sakai; Gil Yosipovitch; Tasuku Akiyama (Medical Journals Sweden, 2019)
Abstract is missing (Short Communication)